Digitalization of the Letter of Credit Process: Implications for Business Performance in Trade Finance : Case Study - Tuomela, Teemu (My University, 2025)
International trade processes remain largely manual and paper-based, leading to delays and additional costs for trading parties. The impact is pronounced in the complex ecosystem of trade finance, where the delivery of a single shipment involves multiple participants and entries. This case study examines the digitalization of the letter of credit process from the perspective of an exporting company, focusing on the impact on business efficiency. The study aims to identify potential solutions, the financial and operational impacts, and key obstacles. The primary data for the study consists of semi-structured interviews with representatives of the case company, banks, and freight forwarders. Secondary data includes the case company's system data and process observations. The data is analyzed using thematic and quantitative text analysis methods. Furthermore, the study utilizes scenario analysis based on Monte Carlo simulations to model the effects of electronic documents on the cost structure of the letter of credit process. The results show that attitudes toward digitalization vary among stakeholders. According to regression analysis, positive sentiment among banks is strongly associated with discourse on digital adoption. The most promising solution for an exporting company is the adoption of electronic documents, and specifically the electronic bill of lading. These solutions eliminate the delays and additional work caused by physical documents, supporting the smooth flow of information between parties. Scenario analysis indicates that as the letter of credit process accelerates, the key benefit for the exporting company is realized through the earlier collection of accounts receivable. Moreover, internal and external integrations within the organization play a key role in enabling the adoption of various digital solutions and their seamless operation. Integrations foster system interoperability, information exchange between stakeholders, reduce duplication of work, and lay the foundation for broader automation. In the long term, automation and artificial intelligence will enhance operational efficiency in support processes, but their systematic utilization requires data standardization and technological maturity. The study shows that creating broad value in the trade finance ecosystem requires a common legal framework that enables data transfer, the harmonization of business data standards, and the commitment of the entire supply chain to digitalization.

Kansainväliset kauppaprosessit toimivat edelleen suurelta osin manuaalisesti ja paperipohjaisesti, mikä aiheuttaa viiveitä ja lisäkustannuksia kaupankäynnin osapuolille. Vaikutus on korostunut kaupan rahoituksen monimutkaisessa ekosysteemissä, jossa yksittäisen hyödykkeen toimitukseen liittyy useita eri toimijoita ja kirjauksia. Tämä tapaustutkimus tarkastelee remburssiprosessin digitalisaatiota viejäyrityksen näkökulmasta keskittyen liiketoiminnan tehokkuuteen kohdistuviin vaikutuksiin. Tutkimuksen tavoitteena on tunnistaa potentiaaliset ratkaisut, taloudelliset ja operatiiviset vaikutukset, sekä keskeiset esteet. Tutkimuksen ensisijaisena aineistona ovat puolistrukturoidut haastattelut tapausyrityksen, pankkien ja huolitsijoiden edustajien kanssa. Toissijaisena aineistona hyödynnetään tapausyrityksen järjestelmädataa ja havainnointia remburssiprosessin kulusta. Aineisto analysoidaan temaattisen ja kvantitatiivisen tekstianalyysin keinoin. Lisäksi tutkimuksessa hyödynnetään Monte Carlo -simulointeihin pohjautuvaa skenaarioanalyysiä, jonka avulla mallinnetaan sähköisten asiakirjojen vaikutuksia remburssiprosessin kustannusrakenteeseen. Tulokset osoittavat, että suhtautuminen digitalisaatioon vaihtelee sidosryhmittäin. Regressioanalyysin mukaan pankkien positiivinen sentimentti on vahvasti yhteydessä digitalisaation omaksumiseen liittyvään diskurssiin. Viejäyritykselle lupaavin ratkaisu on sähköisten asiakirjojen, ja erityisesti sähköisen konossementin käyttöönotto. Ratkaisut poistavat fyysisten asiakirjojen aiheuttamat viiveet ja ylimääräisen työn sekä tukevat osapuolten välistä sujuvaa tiedonkulkua. Skenaarioanalyysi osoittaa, että remburssiprosessin nopeutuessa keskeisin hyöty viejäyritykselle realisoituu myyntisaatavien aikaisemman kotiuttamisen seurauksena. Lisäksi organisaation sisäiset ja ulkoiset integraatiot ovat avainasemassa mahdollistaessaan useiden digitaalisten ratkaisujen käyttöönoton ja sujuvan toiminnan. Integraatiot edistävät järjestelmien yhteensopivuutta, sidosryhmien välistä tiedonvaihtoa, vähentävät päällekkäistä työtä ja luovat perustan automaation laajemmalle hyödyntämiselle. Pitkällä aikavälillä automaatio ja tekoäly lisäävät tukiprosessien operatiivista tehokkuutta, mutta niiden systemaattinen hyödyntäminen edellyttää datan standardointia ja teknologioiden kypsymistä. Tutkimus osoittaa, että laajan arvon luominen kaupan rahoituksen ekosysteemissä vaatii datansiirron mahdollistavan yhteisen oikeudellisen kehyksen, yhtenäiset liiketoimintadatan standardit sekä koko toimitusketjun sitoutumisen digitalisaatioon.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance